Engaging and supporting women with chronic kidney disease with pre‐conception decision‐making (including their experiences during COVID 19): A mixed‐methods study protocol. (3rd March 2021) - Phillips, Rhiannon; McLaughlin, Leah; Williams, Denitza; Williams, Helen; Noyes, Jane; Jones, Caron; Oleary, Catherine; Mallett, Carmen; Griffin, Sian
Abstract: Aim: To report a protocol for a qualitative study to better understand the key factors that influence decision making about pregnancy from women's perspectives and to use these data to develop a theoretical model for shared decision‐making tools for the multiple stakeholders. Design: Mixed‐method design using online surveys (with validated components) and purposively sampled follow‐up semi structured interviews. Methods: Funded from September 2020 for 12 months. Online surveys of adult women (aged 18–50) identified via all Wales kidney database (n ≥ 500), additional recruitment through multidisciplinary healthcare professionals, relevant third sector organizations and social media. Follow‐up in‐depth qualitative interviews with n = 30 women. Linear regression models to identify associations between shared decision‐making preferences and clinical and psychosocial variables. Qualitative interviews will use a visual timeline task to empower women in taking control over their narratives. Qualitative data will be fully transcribed and analysed thematically, based around a chronological and theoretical (theoretical domains framework) structure that maps out key challenges and opportunities for improved decision support in the care pathway. Visual timelines will be used during stakeholder consultation activities, to enable us to co‐create a map of current support, gaps in provision, and opportunities for interventions. Quantitative data will be analysed descriptively to characterize our cohort. We will assemble a multidisciplinary shared decision‐making intervention development group and provide ongoing stakeholder consultation activities with patient and public representatives. Discussion: Outcomes will support new learning into; the ways women's knowledge of kidney disease may affect family planning and pregnancy, their needs in terms of psychological and social support, and how they weigh up the pros and cons of starting a family. Impact: Evidence will inform the design of new shared decision‐making tools to better support women with the complex and often emotional decisions about having children while living with kidney disease.